PENGARUH KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA KANTOR KESATUAN BANGSA DAN POLITIK KOTA SIBOLGA - Riwayani Riwayani; Heriyawan Hutagalung (KOLONI, 2023)
This study aims to determine the effect of communication on employee performance at the Office of National Unity and Politics in Sibolga City. The type of research used in this study is a quantitative research method with a descriptive approach. The sample in this study were employees at the Office of National Unity and Politics in the City of Sibolga by distributing questionnaires totaling 32 (thirty two) respondents. The results of the study show that there is an influence of communication on employee performance at the national and political offices of the city of Sibolga. With good employee communication can improve employee performance. From the hypothesis test, it is obtained that the value of t count > from the value of t table (2.107 > 2.045) then the alternative hypothesis (Ha) is accepted, so the hypothesis proposed is acceptable. Keywords: Employee Performance, Communication